Comparative Study of Heavy Metal Concentration in Eggs Originating from Industrial Poultry Farms and Free-Range Hens in Kosovo - H. Aliu; S. Dizman; A. Sinani; G. Hodolli (Journal of Food Quality)
The aim of the present study was to determine the most significant heavy metal concentration in hen eggs, in particular to compare the heavy metal concentration in eggs originating from industrial poultry farms versus free-range hens. The sampling process was carried out between October and December 2018, in the Republic of Kosovo. In total, 22 random egg samples were collected, with 54.5% and 45.5% of samples coming from poultry farms and free-range hens, respectively. The measurements of the heavy metals were taken by inductively coupled plasma mass spectrometry (ICP-MS), using a wide range of elements, and only the most important elements were reported, such as Cr, Mn, Fe, Ni, Cu, Zn, As, Cd, Hg, and Pb within the range of 0.48–8.45, 38.77–289, 4286.59–15383.74, 0.45–144.74, 61.68–550.59, 1078.04–11378.56, 0.29–35.42, 0.27–6.54, and 0.04–1.41 μg kg−1, respectively. This study revealed that the heavy metals in eggs from free-range hens are richer in essential elements such as Mn, Fe, and Zn, while poultry farm eggs contain a higher contribution of Cr, Cd, As, and Pb. However, the daily intake of heavy metals from egg consumption was lower than the WHO-FAO advised provisional daily intake. Therefore, egg consumption does not exceed the safety levels of toxic metals and does not pose any risk to human health.